RESPON UMUR PANEN DAN DOSIS UREA TERHADAP PERTUMBUHAN DAN BIOMASSA SERTA KANDUNGAN BRIX SORGUM SAMURAI VARIETAS II (Sorghum bicolor L. Moench) SEBAGAI PAKAN RUMINANSIA - Harahap, Anwar Efendi; Taslapratama, Irwan; Juliantoni, Jepri; Harianti, Fitri; Ananta, Arfi (Unpad Press, 2025)
Sorghum has potential as a feed crop that has the ability to adapt to high temperature environments. The purpose of the research was to analyze the growth characteristics and biomass production of sorghum variety II at different cutting ages and urea fertilizer concentrations. The research used a complete randomized design pattern (3 x 3) with 3 replications. The first factor was cutting age namely 60, 65, and 70 days. The second factor was urea fertilizer concentration level of 150, 200, and 250 kg ha-1. Parameters observed included growth characteristics including plant height (cm), stem diameter (cm) and leaf length (cm), then biomass production including fresh biomass production (tons ha-1), and brix content (%). The results showed that each cutting age and urea fertilizer concentration were significantly different (P<0.05) on plant height, stem diameter and leaf length. Furthermore, biomass production and sugar content value (brix) were not influenced by (P>0.05) cutting age and urea fertilizer concentration on sorghum samurai variety II. Cutting age of 70 days and urea concentration of 250 kg ha-1 were the best treatments because they showed superior values in the observation of plant height and stem diameter as well as fresh biomass production